Analisis Perbaikan Efektivitas Organisasi Berbasis McKinsey 7S Framework pada Department Business Process Innovation - Trifenaus Prabu Hidayat; Andre Sugioko; Gabriel Santu Ario Saragih (Metris: Jurnal Sains dan Teknologi, 2026)
This research was conducted in the Business Process Innovation (BPI) Department of PT XYZ, by assessing the effectiveness of the organizational structure and its role in supporting innovation performance. Key issues were identified, including suboptimal cross-functional coordination, inconsistent SOP compliance, and staff competency gaps in process analysis and innovation management. The McKinsey 7S Framework was used, supported by the Balanced Scorecard, RACI Analysis, and Competency Gap Analysis. The results indicate that organizational strategy and systems are scored; however, the innovation culture has not been uniformly implemented, and a largely directive leadership style tends to restrict collaboration. Proposed solutions include strengthening inter-unit coordination, developing project-based competencies, and adopting a more participative leadership approach. These improvements are expected to enhance organizational effectiveness and support sustainable innovation.